Using Real World Problems in Developing Students' Mathematical Skills (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this article, the Diophantine equations, which can be solved in integers, and other vital and practical problems, aimed at making students interested in mathematics and developing their mathematical skills, are considered, and their solution is explained using interesting and simple methods